PELATIHAN PEMBELAJARAN WRITING DENGAN MENGGUNAKAN GAME KEPADA GURU-GURU BAHASA INGGRIS DI KECAMATAN JALAN CAGAK KABUPATEN SUBANG - Yugafiati, Rasi; Kareviati, Evie; Resmini, Setya (Abdimas Siliwangi, 2020)
Teaching English is not an easy one. Furthermore, writing is still considered difficult because the teacher focuses on the National Examination. In order to make writing a subject as an interesting thing, the teacher should have a creative method. in this article, the writer wants to deliver the importance of media to the English teachers in Subang, to make them aware that there are still many things to do to make the subject easier. And it is only needed simple things such as paper or newspaper. The interview is also held to know the response of the teachers. And the results show that the teachers are enthusiastic and realize that they can do simple things to improve their way of teaching English, especially writing.Â